Consumer protection in the perspective of Law of the Republic of Indonesia Number 8 Year 1999 and the perspective of islamic law for users of boat transportation services in Medang Hamlet, West Secotong Village - Khafifi, Ulul Azmi (Ex Aequo Et Bono Journal Of Law, 2024)
Background: This research aims to determine the existence of consumer protection according to the perspective of Law of the Republic of Indonesia Number 8 of 1999 and the perspective of Islamic law on boat transportation in Medang hamlet, Sekotong Barat village which includes the practices, rights and obligations of business actors in running their business and the rights and obligations of consumers, and how to view law no. 8 of 1999 and what is the perspective of Islamic law. Methods: This type of research uses qualitative research, the data collection methods used are observation, interviews and documentation, with data analysis techniques, namely data collection, data reduction, data display and drawing conclusions and verification. Findings: Based on the research results, it can be concluded that business actors in Medang hamlet, Sekotong Barat village are not running their businesses well based on Law no. 8 of 1999 and Islamic law, this is due to the unawareness of business actors and consumers. Conclusion: In their business practices, business actors never provide information about the suitability of the transportation used to consumers, this is done because business actors always prioritize consumer satisfaction over safety, there is no compensation for compensation for consumer goods. All of these things are based on the ignorance of business actors and consumers regarding existing legislation and Islamic law. Novelty/Originality of this Study: This study provides a comparative analysis of consumer protection under Indonesian law and Islamic law, specifically for boat transportation services in Medang Hamlet. It highlights the practical shortcomings and legal non-compliance of local business actors, offering unique insights into the effectiveness of both legal frameworks in a maritime context.